2011
DOI: 10.1103/physrevd.83.096006
|View full text |Cite
|
Sign up to set email alerts
|

Covariant study of tensor mesons

Abstract: We investigate tensor mesons as quark-antiquark bound states in a fully covariant Bethe-Salpeter equation. As a first concrete step we report results for masses of J P C = 2 ++ mesons from the chiral limit up to bottomonium and sketch a comparison to experimental data. All covariant structures of the fermion-antifermion system are taken into account and their roles and importance discussed in two different bases. We also present the general construction principle for covariant Bethe-Salpeter amplitudes of meso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 61 publications
1
77
0
Order By: Relevance
“…On the other hand, it is interesting to note that the situation is still acceptable for the lowest-lying tensor mesons with 2 ++ and 3 −− [301,384]; i.e., the states lying on the Regge trajectory J P C = {1 −− , 2 ++ , 3 −− } are well reproduced. In the potential language, what distinguishes these channels from the others is that the tensor force is either vanishing or particularly small.…”
Section: Mesonsmentioning
confidence: 95%
“…On the other hand, it is interesting to note that the situation is still acceptable for the lowest-lying tensor mesons with 2 ++ and 3 −− [301,384]; i.e., the states lying on the Regge trajectory J P C = {1 −− , 2 ++ , 3 −− } are well reproduced. In the potential language, what distinguishes these channels from the others is that the tensor force is either vanishing or particularly small.…”
Section: Mesonsmentioning
confidence: 95%
“…A particular state is characterized by the Poincaré covariant quantum numbers J P(C) (C of course only when it is an eigenstate of the charge conjugation operator), which determines the basis elements to construct the bound state's BSA [78]. At this point, any particular Lorentz frame may be chosen.…”
Section: Th Quark Confinement and The Hadron Spectrummentioning
confidence: 99%
“…On hadron property side, which is usually taken as the calibration to fix the parameter(s) in the DS equation approach, it has been shown that the bare vertex truncation leads to it only accurate for ground-state vector-and isospinnonzero-pseudoscalar mesons [64,66,67] because corrections in these channels largely cancel each other owing to the parameter-free preservation of the Ward-GreenTakahashi (WGT) identities [82][83][84]. The corrections do not cancel in other channels [85][86][87][88], studies based on such a truncation have thus provided usually poor results for scalar, axial-vector and exotic state mesons [89][90][91][92][93][94], and exhibited gross sensitivity to model parameters for excited states [93][94][95][96] and tensor mesons [97].…”
Section: Introductionmentioning
confidence: 99%